2019
DOI: 10.1055/s-0039-1694740
|View full text |Cite|
|
Sign up to set email alerts
|

Doxorubicin-Immersed Skeletal Muscle Grafts Promote Peripheral Nerve Regeneration Across a 10-mm Defect in the Rat Sciatic Nerve

Abstract: Background The treatment of peripheral nerve defects requires bridging materials. Skeletal muscle grafts have been studied as an alternative to nerve autografts because they contain longitudinally aligned basal laminar tubes that are similar to axons. Several pretreatment methods for muscle grafts have promoted axonal regeneration. Here, a new method of doxorubicin pretreatment was used, and the efficacy of the pretreated muscle graft was evaluated in a rat model of a sciatic nerve defect. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…We weighed the 10-mm graft before and after doxorubicin pretreatment and found that the weight was increased by 0.007 mg on average after the procedure. 24 According to the U.S. Food and Drug Administration drug information, a systemic adverse effect is observed at a total cumulative dose of 300 mg/m 2 . Considering the dosage, adverse effects are thus unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We weighed the 10-mm graft before and after doxorubicin pretreatment and found that the weight was increased by 0.007 mg on average after the procedure. 24 According to the U.S. Food and Drug Administration drug information, a systemic adverse effect is observed at a total cumulative dose of 300 mg/m 2 . Considering the dosage, adverse effects are thus unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were assessed with light microscopy or examined using transmission electron microscopy (TEM; Model H-7000; Hitachi High-Technologies, Tokyo, Japan), according to the previous studies. 4 24 The total number of myelinated axons (TAN), the shortest myelinated axon diameter (MAD; a), the shortest axon diameter (AD; b), and the myelin thickness (MT; [a − b]/2) were measured using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen rats were divided into three equal groups: a decellularized nerve graft (DNG) group, a decellularized nerve graft with a vascularized biogenic conduit (DNG-w-VBC) group, and an autologous nerve graft (ANG) group. Right sciatic nerve defect model rats and decellularized nerve grafts were prepared as described in our previous studies (Kaizawa et al, 2016(Kaizawa et al, , 2017Takeuchi et al, 2019). Briefly, the right sciatic nerve was exposed, and a 10-mm nerve segment of the right sciatic nerve was removed.…”
Section: Nerve Defect Model Establishment and Experimental Designmentioning
confidence: 99%